Hubungan Paritas Dengan Tingkat Kecemasan pada Kehamilan Dalam Mengahadapi Persalinan di Puskesmas Kecamatan Cipeucang Pandeglang Banten - Cahyani, Indah; Jannah, Fathul; Arsyad, Muhammad (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Pregnancy often causes a crisis of maturity that can cause anxiety disorders to stress disorders in pregnant women. Pregnancy often causes a crisis of maturity that can cause anxiety disorders to stress disorders in pregnant women. Indonesia is facing childbirth as many as 107 million pregnant women (28.7%) out of 373 million pregnant women who experience anxiety about childbirth. The population of pregnant women on the island of Java in 2012 there were 67,976 pregnant women, while those who experienced anxiety at the time of delivery were 35,587 people (52.3%) (BPS, 2013). The purpose of this study was to determine the relationship between parity and other factors with the level of anxiety in pregnancy in the face of childbirth. This research is an analytical observational quantitative research conducted on pregnant women who check themselves at the Cipeucang sub-district health center with a total of 52 people. There is a significant relationship between parity and the level of anxiety stating that based on the results of the analysis test using the Chi-Square test, it was found that the value of p = 0.000 (p <0.05) which means that there is a significant relationship between Parity and the level of Anxiety in Pregnancy in Facing Childbirth. at the Cipeucang Pandeglang District Health Center, Banten. Pregnant women who have given birth tend to be able to minimize anxiety compared to pregnant women who have never given birth.